Amino acid composition of plant protein-enriched wheat biscuits differentially affects postprandial amino acid responses of overweight/obese compared to normalweight subjects. - Yanni, Amalia E.; Kanata, Maria-Christina; Papaioannou, Varvara; Halabalaki, Maria; Karathanos, Vaios T. (European Journal of Nutrition, 2025)
Purpose: The study investigates whether postprandial amino acid responses differ between normalweight (NW) and overweight/obese (OW) individuals following consumption of plant protein-enriched wheat biscuits with the same protein content but different protein composition. It highlights the importance of developing functional snack products with specific amino acid profile that could benefit individuals with overweight/obesity. Methods: Thirty volunteers (15 NW and 15 OW) participated in an acute, randomized crossover trial, in which they consumed two plant protein–enriched wheat biscuits differing in amino acid profile—one enriched in L-arginine (arginine biscuit, ArgB) and the other in branched-chain amino acids (branched-chain amino acids biscuit, BCAAsB)—as well as a conventional wheat biscuit (CB) in separate sessions with one week intervals. Postprandial amino acids (AAs) responses were measured for 180 min following ingestion. Fasting and postprandial AAs concentrations were determined by Ultra-High Performance Liquid Chromatography coupled with Time-of-Flight Mass Spectrometry (UHPLC-ToF–MS). Results: OW subjects exhibited higher fasting concentrations of methionine, tryptophan and tyrosine (p < 0.05) while NW subjects, higher levels of glutamine (p < 0.05). Postprandial responses of all the determined AAs to enriched biscuits were higher in the NW compared to the OW group with incremental areas under the curve (iAUCs) of alanine, glutamine and threonine reaching statistical significance (p < 0.05). In the OW group, ingestion of BCAAsB resulted also in lower iAUC values of asparagine and serine, while consumption of ArgB led to a lower iAUC of glycine and a higher iAUC of taurine compared to the NW group (p < 0.05). Conclusion: Ingestion of plant protein-enriched wheat biscuits by OW subjects resulted in lower postprandial responses of alanine, glutamine and threonine compared to NW. AAs composition of BCAAs-enriched biscuit resulted also in lower responses of asparagine and serine while that of the L-arg-enriched biscuit, in lower glycine but higher taurine responses in OW compared to NW subjects. Depletion of all the above-mentioned AAs has been recorded in obesity. Higher taurine concentrations can lead in beneficial effects since taurine improves glycemic control and insulin sensitivity and it has shown potential anti-obesity properties. These findings underscore the challenge of designing protein-rich foods that could elicit beneficial metabolic responses for overweight/obese individuals.